Aprendizagem nos ambientes virtuais: uma análise da concepção discente na licenciatura em ciências biológicas a distância da Universidade Federal da Paraíba - Diniz, Ercules Laurentino (2018)
Distance education is a mode that has been gaining more and more adherents, are undergraduate students, professionals in continuing education, employees interested in updating themselves in their field of work, among other subjects, in common among them, the objective of qualifying is based on a course whose main characteristic is flexibility. Among the many courses offered, there are degrees, so that the number of teachers graduated from this modality is growing in our country. At the Federal University of Paraíba, the degree course in Biological Sciences Distance has 11 poles of face-to-face support. The acting as tutor in this course, aroused the interest of the author of the present research in understanding how the students of the Degree in question learn from the virtual environments. Therefore, it is a general objective to understand the student's conception about the virtual environment Moodle in the learning process in the Degree in Distance Biological Sciences of the UFPB. The theoretical-methodological foundation is based on dialectical historical materialism, where the dialectical method contributes to the understanding of the movement and contradictions existing in the process of teacher training at a distance. This is a qualitative research that investigates the conception of five students about the virtual environment Moodle, having as an instrument of information collection, semi-structured interviews. Based on this research, it can be seen that distance education has provided a significant service in the democratization of access to higher education, representing the only opportunity for such a large number of Brazilians to join. However, the way these courses have been developed in some cases, such as the massification of the process, among other reasons by the influence of neoliberal ideas, or the lack of capacity of the majority of the individuals involved in this process to act in virtual environments, has compromised the teaching-learning process. It is hoped that the present work will favor the discussions about learning in virtual learning environments and that attentive listening of the concepts of the subjects interviewed contribute to a better performance in virtual environments.